Get real about sex : the politics and practice of sex education - Alldred, Pam (Educating boys, learning gender., 2007)
Focusing on young people's identities in the classroom, this book employs contemporary theoretical approaches to explore how gender is enacted and experienced by individuals, and how social pressures and government agendas operate at the level of the individual.